2019
DOI: 10.1002/ece3.5653
|View full text |Cite
|
Sign up to set email alerts
|

Floral display and habitat fragmentation: Effects on the reproductive success of the threatened mass‐flowering Conospermum undulatum (Proteaceae)

Abstract: Fragmentation of natural vegetation is currently one of the largest threats to plant populations and their interactions with pollinators. Plant reproductive susceptibility to habitat fragmentation has been investigated in many species; however, the response of wild mass‐flowering species is poorly known, with research limited to mainly boreal plant species. Here, we studied twelve remnant populations of the threatened mass‐flowering shrub Conospermum undulatum in the southwest Australian biodiversity hotspot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…The flowering period usually ranges from late August to late October. In a recent study, Delnevo et al (2019 b ) found that the pollination mechanism in C. undulatum is an effective physical barrier against autogamous selfing, and also found that this species possesses a strongly developed self-incompatibility system that prevents the development of the embryo following geitonogamous selfing. The hermaphroditic flowers are small, measuring ~7 mm in length, with the tube being ~4 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The flowering period usually ranges from late August to late October. In a recent study, Delnevo et al (2019 b ) found that the pollination mechanism in C. undulatum is an effective physical barrier against autogamous selfing, and also found that this species possesses a strongly developed self-incompatibility system that prevents the development of the embryo following geitonogamous selfing. The hermaphroditic flowers are small, measuring ~7 mm in length, with the tube being ~4 mm.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is also contrasting evidence to suggest that increased pollinator abundance or diversity, high visitation rate and/or having generalist pollinators in a plant community can substantially lower the occurrence of pollen limitation (Phillips et al 2010;Wolowski et al 2014). Equally, factors other than pollen limitation, such as size of floral display, can be important determinants of reproductive success (Delnevo et al 2019). It is likely that non-specialised pollination syndrome of our study species has buffered them from pollen limitation.…”
Section: Discussionmentioning
confidence: 81%
“…The native plants at our site were visited by a wide diversity of insect pollinators, and the main pollinator, A. mellifera, acted as a generalist pollinator. In addition, the lack of a significant difference in the number of viable seeds between the B. sessilis bagged treatment and control would usually indicate self-pollination, as is typical of the family (Delnevo et al 2019). However, this result needs to be interpreted with caution due to limited power to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations